Theoretical Description of the Glass Preparation with the Necessary Optical Properties. (4th February 2016) - Kurasov, Victor
Abstract : The method to get the glass media with necessary optical characteristics is proposed. This method is based on inserting a necessary number of heterogeneous centers of given activity into the system. The theoretical description of the nucleation process in such situation is given and the resulting formulas allow choosing the characteristics of heterogeneous centers necessary to get the required optical characteristics of the media.